Paramater on Maternal Delivery Referral Process - Zubaidah Zubaidah; Mohammad Hakimi; Abdul Wahab (Universitas Airlangga, 2012)
Introduction: The rate of maternal mortality in Indonesia according to 2002–2003 Indonesian Demographic and Health Survey (IDHS) was 307 per 100,000 live births. The direct causes of maternal deaths, among others, are prolonged labor, hemorrhage, infection, and preeclampsia. Referral system includes referring responsibility to better facilitated healthcare sites to obtain more adequate services. However, maternal referral process in Banjar District still faces some problems such as referral health providers with inadequate skills of handling emergency cases, insufﬁcient means of transportation, and no referral letter or partograph. Usually, when referred, the pregnant woman is only accompanied by her family so that she is brought to the referral site without being equipped with infusion. The objective of the study was to evaluate the parameter of maternal delivery referral in Ratu Zalekha Martapura District Hospital.Method: This study used observational study with a cross-sectional study design using quantitative and qualitative approaches. Samples were 107 delivering women referred to hospitals selected with non probability sampling. Data were analyzed with Chi-square (χ) and logistic regression test.Result: Quality maternal referral process resulted in healthy women 78.8%. Post delivery women's health was greater in quality maternal referral process (RP = 2.1; 95% CI = 1.28–3.52). Normal delivery had an opportunity towards post delivery women's health (RP = 1.6; 95% CI = 1.13–2.20). In addition, time needed to reach the referral sites and referral birth attendants were signiﬁcantly associated with maternal referral process (p = 0.002 and p = 0.002). Meanwhile, women's condition when referred was insigniﬁcant statistically.Discussion: Quality maternal referral process could likely improve post delivery women's health.Normal delivery affected the women's health condition.